2013
DOI: 10.1149/2.012308jes
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Properties of Manganese Dioxide Phases for Use in Electrochemical Capacitors: Structural Effects on Solid State Diffusion

Abstract: The solid state mass transport characteristics of various manganese dioxide phases has been examined with a focus on their use in electrochemical capacitors. The phases examined included γ-MnO 2 (electrolytic manganese dioxide), β-MnO 2 (Pyrolusite), Ramsdellite, δ-MnO 2 (Birnessite), α-MnO 2 (Cryptomelane) and λ-MnO 2. Diffusion within each phase was examined using electrochemical impedance spectroscopy (EIS) and step potential electrochemical spectroscopy (SPECS). A √ D (where A is surface area and D is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The second one involves the insertion of cations into the bulk manganese oxide particles which is not limited to only the surface in contact with the electrolyte because of mass transport control. 30 Thus, the specific surface area and the kind of cation species, C + , their concentration, and pH (in the case of aqueous solution) must affect the electrochemical behavior. As described by Chu 23 and Toupin et al, 31 the faradaic process is mainly attributed to H + insertion into amorphous or poorly crystallized manganese dioxide with insignificant insertion of alkali cation (Na + ) and H 3 O + ions, whereas highly crystalline layered structure of manganese dioxide is capable of insertion / deinsertion of sodium ions.…”
Section: Resultsmentioning
confidence: 99%
“…The second one involves the insertion of cations into the bulk manganese oxide particles which is not limited to only the surface in contact with the electrolyte because of mass transport control. 30 Thus, the specific surface area and the kind of cation species, C + , their concentration, and pH (in the case of aqueous solution) must affect the electrochemical behavior. As described by Chu 23 and Toupin et al, 31 the faradaic process is mainly attributed to H + insertion into amorphous or poorly crystallized manganese dioxide with insignificant insertion of alkali cation (Na + ) and H 3 O + ions, whereas highly crystalline layered structure of manganese dioxide is capable of insertion / deinsertion of sodium ions.…”
Section: Resultsmentioning
confidence: 99%
“…This method has previously been used to examine the diffusion characteristics of battery cathode materials, particularly with a focus on examining the quasi-equilibrium discharge and charge characteristics, as well as the kinetics of diffusion through the active material structure as a function of applied potential and state of charge [17][18][19][20]. More recently, the SPECS method used in this work has been applied to manganese dioxide electrodes and successfully differentiated between the charge storage contribution from faradaic and non-faradaic processes [21].…”
Section: This Workmentioning
confidence: 99%
“…This process is diffusion limited and as such, would be contributing to the diffusion limited current. However, the transport of small ions through bulk electrolyte is many orders of magnitude faster than the solid state diffusion of protons through manganese dioxide, 14 and therefore has negligible contribution to the diffusional current compared to solid state diffusion. However, the diffusion of aqueous ions through micro-pores is not as fast as through bulk electrolyte, and may therefore be a non-negligible contributing process.…”
Section: Series Resistance (R S ) and Diffusion Limited Capacitance (...mentioning
confidence: 99%
“…Evidence suggests that the rate at which protons and electrons can diffuse through the material affects the magnitude of pseudo-capacitive charge storage since this process enables access to more of the manganese dioxide structure 12,13 Previous work has shown that different manganese dioxide crystal structures have different rates of proton diffusion at different depths of discharge, which has been attributed to the different tunnel structures either facilitating or hindering proton diffusion. 14 However, it has been difficult to determine an exact relationship between proton diffusion and overall performance due to the effects of double layer capacitance. Manganese dioxide phases all have different specific surface areas, meaning the proportion of capacitance attributed to double layer charging is likely to vary significantly.…”
mentioning
confidence: 99%